Platynosomosis in the municipality of Santa Maria, RS, Brazil - diagnosis by cholecystocentesis - Felipe Auatt Batista de Sousa; Alanna Serpa Stolf; Vinicius Nomi Hirata; Silvia Gonzalez Monteiro; Catherine Konrad Nava Calva; Anna Vitória Hörbe; Saulo Tadeu Lemos Pinto Filho; Anne Santos do Amaral (Ciência Rural)
ABSTRACT: Platynosomosis is the main liver and bile duct verminosis in domestic cats. In Brazil, the cases are concentrated in the southeast and northeast regions, with few reports in the south of the country. A four-year-old male feline, mixed breed, with a history of jaundice, hyporexia and abdominal distension, was referred for clinical care. The leukogram showed leukocytosis due to eosinophilia and serum biochemistry showed a marked increase in liver extravasation enzymes. On ultrasound examination, there was marked hepatomegaly and the presence of dilated, tortuous bile ducts, as well as severe fullness of the gallbladder. Coproparasitological examination proved to be inconclusive. The feline then underwent cholecystocentesis in order to determine the etiology of the condition. The cytological examination of the bile fluid revealed parasite structures with a morphology consistent with operculate eggs of Platynosomum spp. The diagnostic conclusion allowed the establishment of appropriate therapy in a timely manner, which enabled the resolution of the problem. This research reported the first case of feline platynosomosis in the municipality of Santa Maria with clinical cure.